Polyethylene oxide-based solid electrolyte as well as preparation method and application thereof

By introducing modified hydroxyapatite nanowires into the polyethylene oxide matrix, the problems of uneven dispersion and weak interface binding force in PEO electrolyte are solved, and a solid electrolyte with high conductivity and electrochemical stability are achieved, which improves the performance of lithium metal batteries.

CN120581685AActive Publication Date: 2025-09-02刘大海
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511080468.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-09-02
Estimated Expiration
2045-08-04

AI Technical Summary

Technical Problem

The existing PEO electrolytes containing HA have problems in lithium metal solid-state batteries with low lithium ion conductivity, easy to form passivation layers at the interface, high interface impedance and poor battery performance, mainly due to uneven dispersion of HA in PEO and weak interface binding force.

Method used

The hydroxyapatite nanowires with grafted urethane groups, ethylene glycol segments and polylactic acid molecular chains are introduced into the polyethylene oxide matrix. The compatibility and interface binding force with polyethylene oxide are improved by modification treatment, and the solid electrolyte prepared has high ionic conductivity and electrochemical stability.

Benefits of technology

With low filler incorporation, the battery shows excellent electrochemical performance. After 100 cycles, the discharge capacity retention rate exceeds 95%, the battery capacity retention rate is high, the conductivity is improved, and the mechanical strength is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120581685A_ABST
    Figure CN120581685A_ABST
Patent Text Reader

Abstract

The invention discloses a polyethylene oxide-based solid electrolyte as well as a preparation method and application thereof, and belongs to the technical field of batteries, the polyethylene oxide-based solid electrolyte comprises a hydroxyapatite nanowire or a hydroxyapatite nanowire grafted with a carbamate group, an ethylene glycol chain segment and a polylactic acid molecular chain, the mass of the hydroxyapatite nanowire or the mass of the hydroxyapatite nanowire grafted with the carbamate group, the ethylene glycol chain segment and the polylactic acid molecular chain is 0.25%-6% of the mass of the polyethylene oxide. The polyethylene oxide-based solid electrolyte can effectively overcome the defect of large polarity difference between traditional hydroxyapatite and polyethylene oxide, has the characteristics of high ionic conductivity and electrochemical stability, can realize high electrochemical performance at a low doping amount, has the filler doping amount as low as 0.25%, can realize that the discharge capacity is kept at 160mAh / g after more than 100 times of circulation, and has a good application prospect. And the battery capacity retention rate exceeds 95%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a polyethylene oxide-based solid electrolyte, a preparation method and an application thereof. Background Art

[0002] Organic polymer electrolytes such as polyethylene oxide (PEO), polybutylene oxide (PBO), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), etc., have been proven to be the most promising organic polymer electrolytes in lithium metal batteries so far due to their excellent flexibility and processability. As the most typical polymer electrolyte, PEO has excellent Li + Transport performance and high dielectric constant make it the most widely studied electrolyte in polymer electrolyte systems. However, its inherent narrow electrochemical window and low ionic conductivity have become the main constraints limiting its application in high voltage and room temperature environments. Currently, the main consideration is to modify it through a series of methods such as material blending (plasticizers, inorganic fillers, MOFs materials), polymer blending, and interface modification to improve the performance of PEO composite solid electrolyte systems.

[0003] Among the current modified materials, hydroxyapatite (HA) is commonly used. Hydroxyapatite is a typical hexagonal crystal with continuous chain channels along the c-axis, which can provide a low-energy path for the rapid migration of lithium ions. When doped into PEO polymer electrolytes, it can interact with PEO to form additional ion transmission paths, further improving the conductivity. At the same time, as a rigid inorganic filler, hydroxyapatite has a high elastic modulus, which can greatly improve the mechanical strength of the electrolyte, effectively block the penetration of lithium dendrites, and improve the safety of lithium-ion batteries. In addition, the thermal stability and interface performance of the electrolyte after doping with HAP are significantly better than those of traditional PEO-based electrolytes.

[0004] While HA can significantly improve the performance of solid-state electrolytes, the inventors discovered during the implementation of the present invention that the prior art suffers from at least the following issues: PEO electrolytes containing HA often have low lithium ion conductivity and are prone to forming passivation layers, such as lithium phosphate layers, at the interface. This is because HA is unevenly dispersed in PEO, prone to agglomeration, and the interfacial bonding between the two is weak. Due to these dispersibility defects and weak interfacial bonding, full batteries containing HA-filled polyethylene oxide-based solid-state electrolytes often exhibit problems such as interfacial defects, high interfacial impedance, and poor battery performance during charge and discharge. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to address the deficiencies of the above-mentioned prior art and provide a polyethylene oxide-based solid electrolyte, a preparation method and an application thereof. The polyethylene oxide-based solid electrolyte has the characteristics of high interface compatibility and interface bonding between the filler and the polyethylene oxide matrix, and has excellent electrochemical performance when used in lithium metal solid-state batteries.

[0006] Compared with the prior art, the present invention has the following advantages:

[0007] 1. The present invention provides a polyethylene oxide-based solid electrolyte, comprising hydroxyapatite nanowires with grafted carbamate groups, ethylene glycol segments, and polylactic acid molecular chains introduced into a polyethylene oxide matrix. This electrolyte effectively overcomes the significant polarity difference between conventional hydroxyapatite and polyethylene oxide, exhibiting high ionic conductivity and electrochemical stability. High electrochemical performance can be achieved at low filler incorporation levels. With a filler incorporation level as low as 0.25%, a discharge capacity of 160 mAh / g can be maintained after more than 100 cycles, with a battery capacity retention rate exceeding 95%.

[0008] 2. The present invention provides a method for preparing a polyethylene oxide-based solid electrolyte using hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains as fillers, comprising sequentially preparing hydroxyapatite nanowires, sequentially grafting carbamate groups, ethylene glycol segments and polylactic acid molecular chains on the hydroxyapatite to modify it, and blending the modified hydroxyapatite nanowires with a polymer matrix. The method includes nanowire modification and blending, wherein each step in the nanowire modification is independent of each other, and the prepared modified nanowires have high purity and stability.

[0009] 3. Preferably, the above preparation method includes sequentially introducing Ca into a precursor solution consisting of deionized water, methanol and oleic acid. 2+ and PO4 3- , forming a hydrothermal reaction system to prepare hydroxyapatite nanowires with long threads, high crystallinity and regular morphology.

[0010] 4. Preferably, the above preparation method includes using hexamethylene diisocyanate as a grafting raw material and grafting carbamate groups on the nanowires under the catalysis of dibutyltin dilaurate, which has a high grafting reaction rate.

[0011] 5. The preparation method of the present invention has a simple process, easily controllable working conditions, and readily available raw materials. It does not require expensive equipment and a harsh reaction environment to achieve the preparation of high-performance solid-state metal batteries and is suitable for industrial production and application.

[0012] The technical solution of the present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the cycle performance curve of the polyethylene oxide-based solid electrolyte in Example 1.

[0014] Figure 2 This is the rate performance curve of the polyethylene oxide-based solid electrolyte of Example 1.

[0015] Figure 3 This is the cycle performance curve of the polyethylene oxide-based solid electrolyte in Example 2.

[0016] Figure 4 This is the rate performance curve of the polyethylene oxide-based solid electrolyte of Example 2.

[0017] Figure 5 The graph shows the cycling performance comparison curves of the polyethylene oxide-based solid electrolytes of Examples 1 to 4 and Comparative Example 1.

[0018] Figure 6 The figure is a comparison curve of the rate performance of the polyethylene oxide-based solid electrolyte of Examples 1 to 4 and Comparative Example 1.

[0019] Figure 7 This is a schematic diagram of the infrared spectrum test results of the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains in Example 2. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of this application to clearly and completely describe the technical solution. Obviously, the embodiments described are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0021] In the following description, the term "and / or" is used to describe the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist simultaneously. A and B can be singular or plural.

[0022] In the following description, the terms "include", "comprising", "having" and "containing" are open-ended terms, meaning including but not limited to.

[0023] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0024] It will be understood by those skilled in the art that the numerical ranges in the examples of the present application are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the ranges. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also included in the present application. The upper and lower limits of these smaller ranges may independently be included or excluded in the range.

[0025] Unless otherwise indicated, the technical / scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which this application belongs. Although this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0026] The technical principle adopted by the present invention is: using hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains as polymer solid electrolyte fillers, it can fully combine the interaction between carbamate groups and ethylene glycol segments and polyethylene oxide and the characteristics of polylactic acid molecular chains to achieve high compatibility at the interface of organic phase and inorganic phase, and the obtained solid electrolyte has high interfacial bonding strength.

[0027] On the one hand, a polyethylene oxide-based solid electrolyte is provided, comprising hydroxyapatite nanowires or hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains, wherein the mass of the hydroxyapatite nanowires or the mass of the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains in the polyethylene oxide-based solid electrolyte is 0.25% to 6% of the mass of the polyethylene oxide; preferably, the mass of the hydroxyapatite nanowires in the polyethylene oxide-based solid electrolyte is 4% of the mass of the polyethylene oxide, or the mass of the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains in the polyethylene oxide-based solid electrolyte is 0.25% of the mass of the polyethylene oxide. In the present invention, the incorporation amount or incorporation mass is used as the mass of the hydroxyapatite nanowires or the mass of the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains as a percentage of the mass of polyethylene oxide. Preferably, when the polyethylene oxide-based solid electrolyte includes hydroxyapatite nanowires, the incorporation mass percentage of the hydroxyapatite nanowires in the polyethylene oxide-based solid electrolyte is 4% to 6%; when the polyethylene oxide-based solid electrolyte includes hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains, the incorporation mass percentage of the hydroxyapatite nanowires in the polyethylene oxide-based solid electrolyte is 0.25% to 6%; the incorporation mass percentage of the hydroxyapatite nanowires in the polyethylene oxide-based solid electrolyte is the mass ratio of the hydroxyapatite nanowires to the polyethylene oxide.

[0028] Hydroxyapatite nanowires, when used as fillers, can be evenly dispersed in the polyethylene oxide matrix and interact with the long polyethylene oxide chains, improving the compatibility between the filler and the matrix. When the filler is hydroxyapatite nanowires grafted with urethane groups, ethylene glycol segments, and polylactic acid molecular chains, the solid electrolyte exhibits even higher battery performance. High electrochemical performance can be achieved with a filler content as low as 0.25%, maintaining a discharge capacity of 160 mAh / g after 100 cycles, with a battery capacity retention rate exceeding 95%.

[0029] When the filler dosage is too high, filler agglomeration or aggregation is likely to occur, the crystallinity increases, and the interface impedance between the filler and PEO increases, resulting in a decrease in the mechanical properties of the PEO-based solid electrolyte, increased brittleness, and obstruction of the ion transmission path, and a decrease in the overall performance of the PEO-based solid electrolyte.

[0030] In some embodiments, a method for preparing hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains comprises:

[0031] Step 1, providing hydroxyapatite nanowires (HA);

[0032] Step 2: Using the hydroxyapatite nanowires and hexamethylene diisocyanate as raw materials and dibutyltin dilaurate as a catalyst, preparing hydroxyapatite nanowires grafted with carbamate groups, and using the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol as raw materials to prepare hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments (E-HA);

[0033] Step 3: L-lactide is connected to the hydroxyapatite nanowire grafted with carbamate groups and ethylene glycol segments through ring-opening polymerization to obtain hydroxyapatite nanowire grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains (EP-HA).

[0034] Hydroxyapatite nanowires are first prepared, and then carbamate groups, ethylene glycol segments and polylactic acid molecular chains are grafted onto the hydroxyapatite in sequence to achieve modification of the hydroxyapatite nanowires. The obtained hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains can significantly improve their compatibility and dispersibility with the matrix after being incorporated into a polyethylene oxide matrix, greatly reduce the influence of the strong polarity of the hydroxyapatite surface on the incorporated polymer matrix, can effectively improve the interfacial bonding force, avoid the generation of interfacial defects and impedance, and the polyethylene oxide solid electrolyte using it as a filler has high electrochemical stability.

[0035] The processes of preparing hydroxyapatite nanowires, obtaining hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments, and obtaining hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains are carried out step by step to achieve staged modification of hydroxyapatite. Each step of the reaction is carried out independently to effectively avoid interference from side reactions. At the same time, the products of each step are purified by washing and centrifugal drying to avoid the influence of unreacted monomers, catalyst residues or by-products on the next step. The product has the characteristics of high purity, stable performance and structure.

[0036] In some specific embodiments, providing hydroxyapatite nanowires specifically includes:

[0037] Step 1: Mix deionized water, methanol and oleic acid to obtain a precursor solution;

[0038] Step 2: NaOH solution, CaCl2 solution and NaH2PO4•2H2O solution are sequentially added dropwise into the precursor solution and mixed to obtain a precursor solution containing an ion source;

[0039] Step 3: reacting the precursor solution containing the ion source at a temperature of 60-300° C. for 12-36 hours;

[0040] Step 4: Cool the reaction system to room temperature, wash it alternately with anhydrous ethanol and deionized water, centrifuge it, and dry it to constant weight to obtain a white solid, which is hydroxyapatite nanowires (HA); the endpoint of the alternating washing is that the liquid phase after washing is neutral, and the number of washing times with anhydrous ethanol and deionized water is 3 to 5.

[0041] A precursor solution consisting of deionized water, methanol, and oleic acid was prepared, and then Ca 2+ and PO4 3- , realizing the hydrothermal preparation of hydroxyapatite nanowires, which have the characteristics of long threads, high crystallinity and regular morphology.

[0042] In some embodiments, the volume ratio of deionized water, methanol and oleic acid is 1: (0.1~3): (0.1~3), and / or the mass percentage concentration of the NaOH solution, the mass percentage concentration of the CaCl2 solution and the mass percentage concentration of the NaH2PO4•2H2O solution are all 1%~10%; and / or the volume ratio of the NaOH solution, the volume of the CaCl2 solution, the volume of the NaH2PO4•2H2O solution and the volume of the precursor solution is 1: (0.2~1): (0.5~1.5): (2~3).

[0043] Furthermore, the present invention controls the volume ratio of deionized water, methanol and oleic acid constituting the precursor solution, and the Ca 2+ and PO4 3- The introduction order of the NaOH solution is adjusted to achieve uniform nucleation and growth of hydroxyapatite crystals, resulting in uniform ultra-long nanowires. When the mass percentage concentration of the NaOH solution is too low or the feed volume is too small, the resulting hydroxyapatite nanowires are of low purity and contain calcium impurities. If the mass percentage concentration of the NaOH solution is too high or the feed volume is too large, the resulting hydroxyapatite contains sodium impurities. When the mass percentage concentration of the CaCl2 solution is too high or the feed volume is too large, hydroxyapatite nanowires cannot be prepared. When the mass percentage concentration of the CaCl2 solution is too low or the feed volume is too small, the hydroxyapatite yield is seriously affected. When the mass percentage concentration of the NaH2PO4•2H2O solution is too high or the feed volume is too large, the product morphology is severely damaged. When the mass percentage concentration of the NaH2PO4•2H2O solution is too low or the feed volume is too small, impurities remain in the product.

[0044] In some specific embodiments, the preparation of hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments specifically includes:

[0045] Step 1: mixing hydroxyapatite nanowire powder with N,N-dimethylformamide to obtain a hydroxyapatite nanowire system;

[0046] Step 2: adding hexamethylene diisocyanate and dibutyltin dilaurate to the hydroxyapatite nanowire system and reacting them in an oil bath at 50-100° C.;

[0047] Step 3: Add ethylene glycol to the reaction system in step 2 and react in an oil bath at 60-300°C;

[0048] Step 4: Wash the reaction product of step 3, centrifuge, and dry to obtain hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments.

[0049] Hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments are obtained in the order of grafting carbamate groups first and then grafting ethylene glycol segments. Hexamethylene diisocyanate is used as a carbamate group source, and a hydroxyl reaction is achieved on the surface of the hydroxyapatite nanowire under the catalysis of dibutyltin dilaurate to introduce carbamate groups. Ethylene glycol is then added to react under oil bath conditions to achieve grafting of ethylene glycol segments, thereby obtaining hydroxyapatite nanowires modified with specific organic segments, thereby improving their dispersibility and interfacial bonding strength with polyethylene oxide.

[0050] The surface hydroxyl reaction is carried out under the action of dibutyltin dilaurate catalyst, which can effectively reduce the reaction activation energy of the surface hydroxyl reaction, promote the formation of new bonds, accelerate the grafting reaction of hexamethylene diisocyanate and hydroxyapatite, and improve the modification efficiency.

[0051] In some embodiments, in the hydroxyapatite nanowire system, the volume of N,N-dimethylformamide is 20 to 200 times the mass of the hydroxyapatite nanowires, the volume unit of N,N-dimethylformamide is mL, and the mass unit of hydroxyapatite nanowires is g; and / or, the mass of the hexamethylene diisocyanate is 10 to 50 times the mass of dibutyltin dilaurate; and / or, the mass of the hexamethylene diisocyanate is 0.15 to 0.55 times the mass of the hydroxyapatite nanowires; and / or, the reaction time under the oil bath conditions in step 2 is 4 to 10 hours; and / or, the mass of ethylene glycol is 0.08 to 0.3 times the mass of the hydroxyapatite nanowires; and / or, the reaction time under the oil bath conditions in step 3 is 12 to 36 hours.

[0052] In the present invention, it is further preferred that the volume of N,N-dimethylformamide is 20 to 200 times the mass of the hydroxyapatite nanowires, which can ensure that the hydroxyapatite is fully dispersed in the reaction system and that hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments can be efficiently obtained subsequently. When the volume of N,N-dimethylformamide is too large, the efficiency of obtaining the grafted product is low, and when the volume of N,N-dimethylformamide is too small, the hydroxyapatite in the reaction system is unevenly dispersed; dibutyltin dilaurate acts as a catalyst, affecting the reaction rate. When the amount of dibutyltin dilaurate is too large, it will react with hexamethylene diisocyanate instead; hexamethylene diisocyanate is one of the cores of the grafting reaction, and its addition amount directly affects the morphology of the end product. Excessive addition may generate by-products, and too little addition will affect the grafting efficiency; ethylene glycol directly affects the compatibility of the grafted product with the polymer PEO matrix. If too much ethylene glycol is grafted, the grafted product is difficult to disperse in the polymer PEO matrix.

[0053] In some specific embodiments, the preparation of hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains specifically includes:

[0054] Step 1: Mixing hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments, L-lactide, toluene, and stannous octoate to obtain a mixed system A;

[0055] Step 2: reacting the mixed system A in an oil bath at 60-300° C. under stirring;

[0056] Step 3: washing the reaction product with chloroform, centrifuging, and drying to obtain hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains.

[0057] In the present invention, L-lactide is used as a modification raw material to further modify hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments. As a typical cyclic molecule, L-lactide is a cyclic ester formed by the esterification reaction of two lactic acid molecules. During the reaction, under the catalysis of stannous octoate, the L-lactide ring is opened, and the carbamate serves as the initiation site. Through covalent bonds, the polylactic acid molecular chain is connected to the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments, giving the hydroxyapatite nanowires a rigid structural unit.

[0058] In some embodiments, the mass of the L-lactide is 1 to 10 times the mass of the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments; and / or the mass of the toluene is 1000 to 2000 times the mass of stannous octoate; and / or the mass of the stannous octoate is 2% to 4% of the mass of the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments; and / or, in step 2, the reaction time under oil bath conditions is 12 to 36 hours.

[0059] Furthermore, in the present invention, the mass of L-lactide is 1 to 10 times the mass of the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments. Too little L-lactide can shorten the polylactic acid chains or incompletely cover the grafted hydroxyapatite nanowires, affecting their compatibility with the PEO substrate. However, excessive L-lactide can cause the polylactic acid chains to entangle with the PEO chains, hindering lithium ion transport. Stannous octoate is used as a catalyst. When the mass of stannous octoate is 2% to 4% of the mass of the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments, the reaction is fully promoted, avoiding overcatalysis or impurities.

[0060] In some embodiments, the method for preparing the polyethylene oxide-based solid electrolyte further comprises:

[0061] Step 1: placing hydroxyapatite nanowires or hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains in an acetonitrile solution containing polyethylene oxide, and dispersing them by ultrasonication to obtain a mixed system C;

[0062] Step 2: Under an inert atmosphere, add lithium bis(trifluoromethanesulfonyl)imide to the mixed system C and mix well to obtain a mixed system D;

[0063] Step 3: Place the mixed system D in a solid electrolyte mold and dry it under vacuum conditions at 50-100°C to obtain an electrolyte membrane, i.e., a polyethylene oxide-based solid electrolyte.

[0064] The filler is incorporated into the polymer matrix by mixing hydroxyapatite nanowires or hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains with an acetonitrile solution containing polyethylene oxide, blending with lithium bis(trifluoromethanesulfonyl)imide under an inert atmosphere, and vacuum drying.

[0065] In some embodiments, the weight percentage of hydroxyapatite nanowires or hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains in the mixed system C is 0.01% to 10%; and / or the concentration of polyethylene oxide in the acetonitrile solution containing polyethylene oxide is 0.05 g / mL; and / or the ratio of the mass of lithium bis(trifluoromethanesulfonyl)imide to the mass of polyethylene oxide is 1:(1.8-2.8); and / or the drying time under vacuum conditions is 4 to 10 hours; and / or the gas in the inert atmosphere is one or more of helium, nitrogen, argon, and neon. In some specific embodiments, the polyethylene oxide has a molecular weight of 60W and was purchased from Aladdin.

[0066] On the other hand, a solid-state battery is provided, comprising a Li working electrode, a LiFePO4 counter electrode and the above-mentioned polyethylene oxide-based solid electrolyte.

[0067] The present invention has been subjected to a series of experiments before the application is filed. Some of the experimental results are listed below to further describe the invention in detail, and the following embodiments are used to describe the invention in detail.

[0068] Example 1

[0069] This embodiment provides a polyethylene oxide-based solid electrolyte, including hydroxyapatite nanowires. The polyethylene oxide-based solid electrolyte has an incorporation amount of 4% hydroxyapatite nanowires. The incorporation amount of hydroxyapatite nanowires is the ratio of the mass of the hydroxyapatite nanowires to the mass of the polyethylene oxide.

[0070] This embodiment also provides a method for preparing the above-mentioned polyethylene oxide-based solid electrolyte, comprising:

[0071] Step 1: Mix 27 mL of deionized water, 12 mL of methanol, and 21 mL of oleic acid, and stir thoroughly to obtain a precursor solution;

[0072] Step 2: Prepare a 6.54% NaOH solution, a 2.7% CaCl2 solution, and a 3.85% NaH2PO4•2H2O solution;

[0073] Step 3: 30 mL of the NaOH solution, 24 mL of the CaCl2 solution, and 36 mL of the NaH2PO4•2H2O solution were sequentially added dropwise to the precursor solution, and stirred thoroughly until mixed to obtain a precursor solution containing an ion source;

[0074] Step 4: The precursor solution containing the ion source was placed in a 100 mL reaction kettle and placed in an oven at 180° C. for 24 h;

[0075] Step 5: Cool the reactor to room temperature, wash alternately with anhydrous ethanol and deionized water, centrifuge, and dry to constant weight to obtain a white solid, which is then ground to obtain hydroxyapatite nanowire powder (HA); wash with anhydrous ethanol and deionized water three times each;

[0076] Step 6: 0.032 g of hydroxyapatite nanowire powder was placed in 16 mL of an acetonitrile solution containing polyethylene oxide, and dispersed by ultrasonication to obtain a mixed system C; the concentration of polyethylene oxide in the 16 mL of the acetonitrile solution containing polyethylene oxide was 0.05 g / mL; the polyethylene oxide had a molecular weight of 60 w and was purchased from Aladdin;

[0077] Step 7: In a glove box filled with helium atmosphere, add 0.348 g of lithium bis(trifluoromethanesulfonyl)imide to the mixed system C and mix well to obtain a mixed system D;

[0078] Step 8: Place the mixed system D in a solid electrolyte mold and dry it at 60° C. under vacuum conditions for 8 h to obtain an electrolyte membrane, namely, a polyethylene oxide-based solid electrolyte.

[0079] The polyethylene oxide-based solid electrolyte was used as the solid electrolyte, Li as the working electrode, and LiFePO4 as the counter electrode to assemble a button cell. The charge and discharge cycle test was carried out using a NEWARE battery test system at a test temperature of 60°C. Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the reversible capacities are 166.3, 165.2, 160.1, 20.2, and 1.3 mAh / g at 0.1, 0.2, 0.5, 1, and 2 C, respectively. At a current density of 0.1 A / g, the discharge specific capacity can be maintained at 162.3 mAh / g after 105 cycles, and the battery capacity retention rate reaches 95.6%.

[0080] Example 2

[0081] This embodiment provides a polyethylene oxide-based solid electrolyte, comprising hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains. In the polyethylene oxide-based solid electrolyte, the amount of hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains incorporated is 0.25%.

[0082] This embodiment also provides a method for preparing the above-mentioned polyethylene oxide-based solid electrolyte, comprising:

[0083] Step 1: Providing hydroxyapatite nanowires (HA), specifically comprising:

[0084] Step 101: Mix 27 mL of deionized water, 12 mL of methanol, and 21 mL of oleic acid, and stir thoroughly until the mixture is uniform to obtain a precursor solution;

[0085] Step 102: Prepare a 6.54% by mass NaOH solution, a 2.7% by mass CaCl2 solution, and a 3.85% by mass NaH2PO4•2H2O solution;

[0086] Step 103: 30 mL of the NaOH solution, 24 mL of the CaCl2 solution, and 36 mL of the NaH2PO4.2H2O solution are sequentially added dropwise to the precursor solution, and the mixture is stirred thoroughly until uniformly mixed, thereby obtaining a precursor solution containing an ion source.

[0087] Step 104: Place the precursor solution containing the ion source into a 100 mL reactor and place it in an oven at 180° C. for 24 hours;

[0088] Step 105: Cool the reactor to room temperature, wash alternately with anhydrous ethanol and deionized water, centrifuge, and dry to constant weight to obtain a white solid, which is then ground to obtain hydroxyapatite nanowire powder (HA); wash with anhydrous ethanol and deionized water three times each;

[0089] Step 2: Using the hydroxyapatite nanowires and hexamethylene diisocyanate as raw materials and dibutyltin dilaurate as a catalyst, preparing hydroxyapatite nanowires grafted with carbamate groups, and using the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol as raw materials to prepare hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments (E-HA), specifically comprising:

[0090] Step 201: 1 g of the hydroxyapatite nanowire powder and 40 mL of N,N-dimethylformamide (DMF) are placed in a dehydrated and deoxygenated reaction bottle, and mixed by ultrasonication to obtain a hydroxyapatite nanowire system;

[0091] Step 202: Add 0.52 g of hexamethylene diisocyanate and 0.015 g of dibutyltin dilaurate to the hydroxyapatite nanowire system, and stir the mixture in an oil bath at 50° C. under nitrogen protection for 8 h.

[0092] Step 203: Add 0.289 g of ethylene glycol to the reaction mixture in step 2, and stir the mixture in an oil bath at 60° C. for 12 h.

[0093] Step 204: washing the reaction product of step 203 alternately with toluene and DMF, centrifuging, and drying to a constant weight to obtain hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments;

[0094] Step 3: Using hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments and L-lactide as main raw materials, L-lactide is connected to the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments through ring-opening polymerization to prepare hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains (EP-HA), which specifically includes:

[0095] Step 301: 0.4 g of hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments and 1.333 g of L-lactide were placed in a dehydrated and deoxygenated reaction bottle, and 26.1 g of toluene and 0.015 g of stannous octoate were added to obtain a mixed system A.

[0096] Step 302: Under nitrogen protection and magnetic stirring, the mixed system A is reacted in an oil bath at 120° C. for 24 hours;

[0097] Step 303: washing the reaction product with chloroform, centrifuging, and drying to obtain a modified product of hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains (EP-HA);

[0098] Step 4: adding EP-HA to polyethylene oxide to obtain a polyethylene oxide-based solid electrolyte, specifically comprising:

[0099] Step 401: 0.002 g of EP-HA powder was placed in 16 mL of an acetonitrile solution containing polyethylene oxide, and dispersed by ultrasonication to obtain a mixed system C; the concentration of polyethylene oxide in the acetonitrile solution containing polyethylene oxide was 0.05 g / mL; the polyethylene oxide had a molecular weight of 60 w and was purchased from Aladdin;

[0100] Step 402: In a glove box filled with helium atmosphere, add 0.348 g of lithium bis(trifluoromethanesulfonyl)imide to the mixed system C and mix well to obtain a mixed system D;

[0101] Step 403: Place the mixed system D in a solid electrolyte mold and dry it at 80° C. under vacuum conditions for 8 hours to obtain an electrolyte membrane, namely, a polyethylene oxide-based solid electrolyte.

[0102] The polyethylene oxide-based solid electrolyte was used as the solid electrolyte, Li as the working electrode, and LiFePO4 as the counter electrode to assemble a button cell. The charge and discharge cycle test was carried out using a NEWARE battery test system at a test temperature of 60°C. Figure 3 and Figure 4 As shown. Figure 3 and Figure 4It can be seen that the reversible capacities are 164.5, 163.7, 160.6, 137.7 and 17.3 mAh / g at 0.1, 0.2, 0.5, 1 and 2 C respectively. At a current density of 0.1 A / g, the discharge specific capacity can be maintained at 160.4 mAh / g after 100 cycles, and the battery capacity retention rate is 95.6%.

[0103] Comparative Example 1

[0104] This comparative example examines the effect of hydroxyapatite nanowires or hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains on the performance of polyethylene oxide-based solid electrolytes. The preparation method of the polyethylene oxide-based solid electrolyte provided in this comparative example includes:

[0105] In a glove box filled with helium atmosphere, 0.348 g of lithium bis(trifluoromethanesulfonyl)imide was added to an acetonitrile solution containing polyethylene oxide, and the mixture was mixed to obtain a mixed system; the acetonitrile solution containing polyethylene oxide was the same as that in Example 1;

[0106] The mixed system was placed in a solid electrolyte mold and dried at 80° C. under vacuum conditions for 8 hours to obtain an electrolyte membrane, namely, a polyethylene oxide-based solid electrolyte.

[0107] The polyethylene oxide-based solid electrolyte of this comparative example is assembled into a battery and the testing method is the same as that of Example 1. The results show that at 0.1, 0.2, 0.5, 1 and 2C, the reversible capacity is 139.2, 120.6, 2.1, 0.6, and 0.04 mAh / g, respectively. At a current density of 0.1A / g, the capacity remains at 138.6 mAh / g after 100 cycles, and the battery capacity retention rate is only 90.3%. The electrochemical performance of the polyethylene oxide-based solid electrolyte assembled full battery of Example 1 is compared with that of Comparative Example 1. In the range of 0.1~2C, it has a reversible capacity higher than that of the comparative example, especially when the current density is 0.1~0.5C. As the rate increases, the reversible capacity decay is significantly lower than that of Comparative Example 1, indicating that the present invention can effectively improve the reversible capacity of the full battery and the solid electrolyte has a significantly improved interface compatibility. Compared with Comparative Example 1, the battery capacity retention rate of the full battery assembled with the polyethylene oxide-based solid electrolyte in Example 1 is as high as 95.6% after 105 cycles at a current density of 0.1 A / g, which is significantly higher than the battery capacity retention rate of Comparative Example 1, indicating that the present invention can effectively improve the long-cycle stability of the full battery.

[0108] Example 3

[0109] This example examines the effect of the amount of hydroxyapatite nanowires incorporated on the performance of a polyethylene oxide-based solid electrolyte. The preparation method is the same as that of Example 1, except that in step six, the mass of the hydroxyapatite nanowires is 0.016 g.

[0110] The assembly of the polyethylene oxide-based solid electrolyte into a battery and the testing method of this embodiment are the same as those of Example 1. The results show that at 0.1, 0.2, 0.5, 1 and 2C, the reversible capacity is 165.2, 157.3, 140.5, 13.2 and 0.9 mAh / g, respectively. At a current density of 0.1C, the capacity can be maintained at 154.3 mAh / g after 100 cycles, and the battery capacity retention rate is 93.4%. In combination with Example 1 and Example 3, it can be seen that the full battery assembled with the polyethylene oxide-based solid electrolyte obtained by introducing hydroxyapatite into the polyethylene oxide matrix using the method of the present invention has a reduced long-cycle battery capacity retention rate when the hydroxyapatite incorporation amount is 2%.

[0111] Example 4

[0112] This example examines the effect of the incorporation amount of hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains on the performance of a polyethylene oxide-based solid electrolyte. The preparation method is the same as that of Example 2, except that in step 401, the mass of the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains is 0.004 g.

[0113] The assembly of the polyethylene oxide-based solid electrolyte into a battery and the testing method of this embodiment are the same as those of Example 2. The results show that at 0.1, 0.2, 0.5, 1 and 2C, the reversible capacity is 145.3, 131.3, 3.1, 0.7 and 0.01 mAh / g, respectively. At a current density of 0.1A / g, the capacity can be maintained at 148.6 mAh / g after 100 cycles, and the battery capacity retention rate is only 92.3%, which is lower than that of Example 2. Comparing Example 2 with Example 4, it can be seen that the polyethylene oxide-based solid electrolyte assembled full battery of Example 2 has a higher reversible capacity than that of Example 4 in the range of 0.1~2C. Within this range, as the rate increases, the reversible attenuation is significantly lower than that of Example 4, indicating that the present invention can effectively improve the reversible capacity of the full battery, and the prepared solid electrolyte has significantly improved interface compatibility. The comparison results of the electrochemical properties of the polyethylene oxide-based solid electrolytes of Examples 1~4 and Comparative Example 1 are shown in Figure 2. Figure 5 and Figure 6 As shown, PEO+4% HA refers to Example 1, PEO+0.25% EP-HA refers to Example 2, PEO refers to Comparative Example 1, PEO+2% HA refers to Example 3, and PEO+0.5% EP-HA refers to Example 4.

[0114] Structural evaluation

[0115] The Fourier transform infrared spectra of the hydroxyapatite nanowires (HA) of Example 2, the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments (E-HA), and the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains (EP-HA) are as follows: Figure 7 As shown, it can be seen that all three spectral lines belong to phosphate PO4 3- The vibration peak is located at 1026cm -1 and 1080cm -1 , 3570cm in HA -1 There is also a vibration peak attributable to the hydroxyl group -OH; in E-HA and EP-HA, 2856cm -1 and 2931cm -1 The peak at -(CH2)6 is attributed to hexamethyl diisocyanate - Chain segment, 1250cm -1 The peak position is attributed to the CN stretching vibration of the carbamate bond (-NHCOO-), 1600 cm -1 NH bending vibration peak of carbamate bond (-NHCOO-), 1630 cm -1 The C=O stretching vibration of the carbamate bond (-NHCOO-) is obtained. Hexamethylene diisocyanate (OCN-(CH2)6-NCO) itself does not contain a carbamate bond. The two terminal hydroxyl groups of ethylene glycol (HO-CH2-CH2-OH) react with the isocyanate group (-NCO) of hexamethylene diisocyanate to form a carbamate bond (-NHCOO-), indicating that the ethylene glycol grafting is successful. On the EP-HA spectrum, 1750 cm -1 The C=O stretching vibration peak of the ester bond of polylactic acid (PLA) appears at 1200 cm -1 The characteristic peak appearing at is attributed to the COC asymmetric stretching vibration, indicating that the polylactic acid molecular chain was successfully grafted into EP-HA.

Claims

1. A polyethylene oxide-based solid electrolyte, characterized in that: The invention relates to a hydroxyapatite nanowire or a hydroxyapatite nanowire grafted with a carbamate group, an ethylene glycol segment and a polylactic acid molecular chain. In the polyethylene oxide-based solid electrolyte, the mass of the hydroxyapatite nanowire or the mass of the hydroxyapatite nanowire grafted with a carbamate group, an ethylene glycol segment and a polylactic acid molecular chain is 0.25% to 6% of the mass of the polyethylene oxide.

2. The polyethylene oxide-based solid electrolyte according to claim 1, characterized in that The preparation method of the hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains comprises: providing hydroxyapatite nanowires; Using the hydroxyapatite nanowires and hexamethylene diisocyanate as raw materials and dibutyltin dilaurate as a catalyst, hydroxyapatite nanowires grafted with carbamate groups are prepared; using the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol as raw materials, hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments are prepared; L-lactide is connected to the hydroxyapatite nanowire grafted with carbamate groups and ethylene glycol segments through ring-opening polymerization to obtain hydroxyapatite nanowire grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains.

3. The polyethylene oxide-based solid electrolyte according to claim 2, characterized in that Providing hydroxyapatite nanowires specifically includes: Step 1: Mix deionized water, methanol and oleic acid to obtain a precursor solution; Step 2: NaOH solution, CaCl2 solution and NaH2PO4•2H2O solution are sequentially added dropwise into the precursor solution and mixed to obtain a precursor solution containing an ion source; Step 3: reacting the precursor solution containing the ion source at a temperature of 60-300° C. for 12-36 hours; Step 4: Cool the reaction system to room temperature, wash, centrifuge, and dry to obtain hydroxyapatite nanowires.

4. The polyethylene oxide-based solid electrolyte according to claim 3, characterized in that The volume ratio of deionized water, methanol and oleic acid is 1:(0.1~3):(0.1~3); and / or, the mass percentage concentration of the NaOH solution, the mass percentage concentration of the CaCl2 solution and the mass percentage concentration of the NaH2PO4•2H2O solution are all 1%~10%; and / or, the volume ratio of the NaOH solution, the volume of the CaCl2 solution, the volume of the NaH2PO4•2H2O solution and the volume ratio of the precursor solution is 1:(0.2~1):(0.5~1.5):(2~3).

5. The polyethylene oxide-based solid electrolyte according to claim 2, characterized in that: The preparation of hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments specifically includes: Step 1: mixing hydroxyapatite nanowires with N,N-dimethylformamide to obtain a hydroxyapatite nanowire system; Step 2: adding hexamethylene diisocyanate and dibutyltin dilaurate to the hydroxyapatite nanowire system and reacting them in an oil bath at 50-100° C.; Step 3: Add ethylene glycol to the reaction system in step 2 and react in an oil bath at 60-300°C; Step 4: Wash the reaction product of step 3, centrifuge, and dry to obtain hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments.

6. The polyethylene oxide-based solid electrolyte according to claim 5, characterized in that In the hydroxyapatite nanowire system, the volume of N,N-dimethylformamide is 20 to 200 times the mass of the hydroxyapatite nanowires, the volume unit of N,N-dimethylformamide is mL, and the mass unit of the hydroxyapatite nanowires is g; and / or, the mass of the hexamethylene diisocyanate is 10 to 50 times the mass of the dibutyltin dilaurate; and / or, the mass of the hexamethylene diisocyanate is 0.15 to 0.55 times the mass of the hydroxyapatite nanowires; and / or, the reaction time under the oil bath conditions in step 2 is 4 to 10 hours; and / or, the mass of ethylene glycol is 0.08 to 0.3 times the mass of the hydroxyapatite nanowires; and / or, the reaction time under the oil bath conditions in step 3 is 12 to 36 hours.

7. The polyethylene oxide-based solid electrolyte according to claim 2, characterized in that: The preparation of hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains specifically includes: Step 1: Mixing hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments, L-lactide, toluene, and stannous octoate to obtain a mixed system A; Step 2: reacting the mixed system A in an oil bath at 60-300° C. under stirring; Step 3: Washing, centrifuging, and drying the reaction product to obtain hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments, and polylactic acid molecular chains.

8. The polyethylene oxide-based solid electrolyte according to claim 7, characterized in that: The mass of the L-lactide is 1 to 10 times the mass of the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments; and / or, the mass of the toluene is 1000 to 2000 times the mass of stannous octoate; and / or, the mass of the stannous octoate is 2% to 4% of the mass of the hydroxyapatite nanowires grafted with carbamate groups and ethylene glycol segments; and / or, in step 2, the reaction time under oil bath conditions is 12 to 36 hours.

9. A method for preparing the polyethylene oxide-based solid electrolyte according to claim 1, characterized in that: include: Step 1: placing hydroxyapatite nanowires or hydroxyapatite nanowires grafted with carbamate groups, ethylene glycol segments and polylactic acid molecular chains in a solution containing polyethylene oxide, and dispersing them by ultrasonication to obtain a mixed system C; Step 2: Under an inert atmosphere, add lithium salt to the mixed system C and mix well to obtain a mixed system D; Step 3: Place the mixed system D in a solid electrolyte mold and dry it under vacuum conditions at 50-100°C to obtain a polyethylene oxide-based solid electrolyte.

10. A full battery, characterized in that: The invention comprises a lithium electrode, a lithium iron phosphate electrode and the polyethylene oxide-based solid electrolyte as claimed in claim 1.

Citation Information

Patent Citations

  • Polyhydroxy nano-material composite solid polymer electrolyte

    CN113851703A

  • High-voltage sandwich-structured gel polymer electrolyte, and preparation method and application thereof

    CN119069265A

  • Lignin-based flame-retardant bacterial cellulose gel polymer electrolyte, preparation and application

    CN120184358A

  • Method for constructing polyethylene oxide-based composite solid electrolyte by sub-nanowires

    CN120319900A

  • Solid polymer electrolyte film

    JP2004339422A